Comparative Study on the Preparation and Gas Sensing Properties of Reduced Graphene Oxide/SnO2 Binary Nanocomposite for Detection of Acetone in Exhaled Breath - Kalidoss, Ramji; Umapathy, Snekhalatha; Anandan, Rohini; Ganesh, Vattikondala; Sivalingam, Yuvaraj (Analytical chemistry (Washington), 2019)
Reduced graphene oxide/tin dioxide (RGO/SnO2) binary nanocomposite for acetone sensing performance was successfully studied and applied in exhaled breath detection. The influence of structural characteristics was explored by synthesizing the composite (RGO/SnO2) using the solvothermal method (GS-I) and the hydrothermal method (GS-II) by the chemical route and mechanical mixing, respectively. The nanocomposites characterized by X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), Fourier transform-infrared spectroscopy (FT-IR), and Brunauer–Emmett–Teller (BET) revealed that GS-I exhibited better surface area, surface energy and showed enhanced gas response than GS-II at an operating temperature of 200 °C. These sensors exhibited comparable response in humid environment as well, suitable for acetone sensing in exhaled breath that clearly distinguishes between healthy and diabetes subjects. The enhanced response at lower concentrations was attributed to the synergistic effect at the RGO/SnO2 interface. These results indicate that modification in the structural characteristics of RGO/SnO2 nanocomposite enhances the sensing property. Furthermore, it proved to be a promising material for potential application for point-of care, noninvasive diabetes detection.